Eu só quero chocolate: um estudo sobre a importância de aspectos pessoais e contextuais no consumo de chocolate - Smith, Marcia Baroni Nader Costa (2010)
Many foods are known only in some human groups, for many reasons. Others, however, became practically universal, and are known and appreciated in almost all societies with economic conditions that allow their inclusion in the realm of international commerce. One of those foods, in particular, is in focus in this investigation. It is not relevant for the composition of every day food habits in any human group, but it certainly takes a central position in terms of preference in various parts of the world: chocolate. This paper aimed to discover and analyze the factors that may influence the consumption of chocolate among a group of people and the way these people justify or explain their consumption pattern and interest for this product. To collect the information an instrument composed of 62 closed questions and 1 open question - which used the technique referred to as free association (evocation) - was used. A group of 313 men and women participated in the survey, most of those aged 16 to 25. Variables such as social and financial situation, body weight, health state, frequency and amount of chocolate consumed, preference regarding consumption of food in general were analyzed, as well as the situations which the participants admitted to be associated with changes in their chocolate consumption pattern, having been included both stressful and relaxing situations. Some points considered controversial regarding the consumption of chocolate, which often appear to be of interest from an academic point of view and the mass media, were also considered. It became clear, in the group analyzed, that many aspects of chocolate consumption are not processed in the same way by men and women. The culturally emphasized fact that women are prone to eat more chocolate than men and that the female choice of foods is more affected by mood and emotional states became evident, which may play a role in the discussion of food disorders and addictions. In agreement with the literature regarding eating behavior, the data obtained support the proposition that it is insufficient to consider only cultural or biological factors, in an isolated manner, to explain why people eat certain foods.